Property Evaluation of Cement-Stabilized Macadam Modified via Phosphorus Slag Materials - Qian, Guoping; Liu, Wei; Gong, Xiangbing; Li, Xi; Zhang, Yalong (Frontiers in Materials, 2022)
Phosphorus slag, known as the waste product of the phosphate ore industry, is causing critical environmental issues due to its direct exposure to natural spaces. In this paper, a partial replacement of the natural fine aggregate ordinarily used in cement-stabilized macadam (CSM) base by phosphorus slag was explored to be an effective solution for phosphorus slag waste. CSM specimens were fabricated by adding various dosages of phosphorus slag particle and fine powder, while the optimum moisture content and maximum dry density were analyzed through compaction tests. Compressive strength, bending tensile strength, fatigue lifespan, dry shrinkage, and temperature shrinkage performance at different curing durations were investigated to evaluate the properties of modified macadam. Results show that phosphorus slag reduced the early compressive strength of CSM to a small extent, but the compressive strength finally increased at 90 days’ curing. The modified slag particles and slag fine powder exhibited different behaviors to repeated loading, moisture loss, and temperature difference. Finally, according to the strength change, fatigue performance comparison, and shrinkage strain caused by the incorporation of phosphorous slag materials into the CSM, it was verified that 25% of the particles and 40% of the fine powder is the best replacement ratio.